ESL design and verification : - Bailey, Brian (Morgan Kaufmann, 2007)
This book arises from experience the authors have gained from years of work as industry practitioners in the Electronic System Level design area; they have seen "SLD" or "ESL" go through many stages and false starts, and have observed that the shift in design methodologies to ESL is finally occurring. This is partly because of ESL technologies themselves are stabilizing on a useful set of languages being standardized (SystemC is the most notable), and use models are being identified that are beginning to get real adoption.